THE ANALYSIS OF LINGUISTIC FEATURES OF MILO ADVERTISEMENT - Ikrimah, Ikrimah; Altalarik, Agel; Luardini, Maria Arina (Universitas PGRI Sumatera Barat, 2024)
An advertisement can be in the form of text, a picture, audio, or video and is intended to promote a certain product. Certainly, an advertisement may be analyzed in terms of the linguistic features that it contains. Linguistic features encompass the utilization of sentence structure, grammatical conventions, and mechanical elements within written communication. This analysis has an intention to find out the linguistic features of Milo advertisement, as well as the visual features, and the relationship between them. The approach that was taken was a form of description that involves monitoring the official advertisement that was available on Youtube platform then the researchers analyzed it. The result showed that there were lexical, morphological, and syntactic aspect appeared, where there were verb phrase, noun phrase, and adjective for lexical and morphological aspect, meanwhile imperative and declarative for syntactic aspect.